Effects of diafenthiuron in toxic baits on colonies of leaf-cutting ants (Hymenoptera: Formicidae) - Barbosa, M. S.; Forti, L. C. [UNESP]; Fujihara, R. T.; Raetano, C. G. (Universidade Estadual de Feira de Santana, 2017)
Dianfenthiuron is a pre-insecticide that can be activated by photolysis, and may be a promising formicide. This study evaluated the effect of diafenthiuron after photolysis in colonies of Atta sexdens rubropilosa Forel, 1908. The experiment was conducted in a completely randomized design with five treatments and five replications: control (no active ingredient), sulfluramid (standard formicide), diafenthiuron (no exposure to UV), diafenthiuron (2h exposure to UV) and diafenthiuron (6h exposure to UV). Toxic baits were applied at a rate of 0.5 g per colony, and we observed the transport and incorporation of the baits into the colonies. A grading scale was used (0 to 4) to measure the cutting of Acalypha L. (Euphorbiaceae) leaves by workers at 2, 7, 14 and 21 days after application (DAA) and we also measured the garden mass (fungus + adult + brood) at 21 DAA in order to check for growth of the fungus culture. Total loading and incorporation occurred one hour after application of the baits. Colonies that received sulfluramid did not transport leaves at 2 DAA. Workers that received baits with D2h showed an average of 20% transport and 55% incorporation of leaves at 21 DAA. The grading scale indicated that treatments D2h and D6h had the lowest averages, 0.80 and 2.00, respectively. The treatments D2h and D6h reduced cutting of leaves and fungus garden mass, but did not kill the colonies of A. sexdens rubropilosa.
Keywords: Atta; Carbodiimide; Chemical control; Ultraviolet light